OBSTACLES OF IMPLEMENTING LEARN FROM HOME PROGRAM FOR JUNIOR HIGH SCHOOL STUDENTS: TEACHERS’ AND PARENTS’ EXPERIENCES - Nur Padhilah; Sri Setyarini; Gin Gin Gustine (Universitas Islam Negeri Alauddin Makassar, 2022)
The global pandemic in the last two years forces the education practitioners in Indonesia to transform the face-to-face learning to distance learning which is a massive change in a sudden time. This article discusses one study that address the phenomena. The study was conducted in junior high school to find the obstacles faced by the EFL teachers and the students’ parent/guardian when applying learn from home program during the pandemic. Online interview was used in the study for investigating the implementation of two teachers, one mother, and one guardian. The findings reveal that the teachers faced obstacles in students’ attitude evaluation, integrity evaluation, teaching duration, students directions, and uncooperative parents. Whereas, the parent/guardian’s obstacle was they couldn’t participate in the learning process maximally due to work schedule. The various obstacles imply inactive cooperation between the teachers and the parents during the program. The findings are directed to provide information to the teaching literature and to improve EFL teaching practice.global pandemic, learn from home, distance learning.